A Nation of Cane, A Nation of Imports: An Analysis of the Determinants of Sugar Import Dependency in Indonesia - Muhamad Emil Rachman; Zainuddin Zainuddin (Jurnal MeA (Media Agribisnis), 2026)
Indonesia, once a major global sugar producer, has become increasingly dependent on imports to meet domestic demand. This study analyzes the determinants of sugar import dependency in Indonesia using an econometric approach. The research utilizes time-series data from 2000 to 2024 and applies model economic Indonesian sugar to examine the effects of key variables, including domestic sugar production, consumption, international sugar prices, exchange rates, and government policies. The findings show that domestic production has a significant negative effect on sugar imports, while consumption and international prices have a positive and significant impact. Exchange rate depreciation is also associated with higher import values. In addition, inconsistent government policies contribute to structural inefficiencies in the sugar sector, further reinforcing import dependency. These results indicate that Indonesia’s reliance on sugar imports is driven not only by the imbalance between domestic supply and demand but also by broader economic and institutional factors. Therefore, policy efforts should focus on increasing agricultural productivity, modernizing sugar processing industries, and ensuring consistent trade regulations. Strengthening these aspects is essential to reduce import dependency and enhance the competitiveness and sustainability of Indonesia’s sugar industry.